Wanprestasi dalam Akad Ijarah pada Platform Jasa Ojek Online: Tinjauan Hukum Ekonomi Syariah - Bunga Lexsa Angelia (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
The rapid development of digital service platforms, particularly online motorcycle taxi services, has transformed modern economic transaction patterns, where the relationship between drivers and consumers is categorized as an ijarah (service lease) contract. However, in practice, various forms of breach of contract (wanprestasi) frequently occur and potentially harm one of the parties. This study aims to analyze the concept of the ijarah contract, identify the forms of wanprestasi, and review them based on Sharia Economic Law principles. This qualitative normative research employs a literature-based approach, utilizing secondary data from classical fiqh books, DSN-MUI fatwas, the Indonesian Civil Code, and reputable academic journals, which are analyzed descriptively-analytically. The findings reveal that breaches occur in three typologies: unilateral cancellation by consumers (ta'addi), negligence and fictitious account manipulation by drivers (taqshir and tadlis), and disproportionate cancel fee policies by platforms, indicating structural dzulm. From a sharia perspective, the settlement of wanprestasi requires compensation (ta'widh) calculated based on actual loss without riba elements, while classifying technical obstacles as force majeure under a fault-based liability approach. This study implies the need to reconstruct the digital ecosystem so that it is not only formally valid but also enforces substantive justice based on maslahah (public interest), al-‘adl (justice), mas,uliyyah (responsibility), and tawazun (proportional balance)